Electronic and optical properties of a novel fluoroaluminate red phosphor Cs2NaAl3F12:Mn4+ with high color purity for white light-emitting diodes. Issue 33 (29th July 2019) - Liang, Zibo; Yang, Zhaofeng; Xie, Xiaoling; Pu, Haiqi; Shi, Dongxin; Zhou, Qiang; Wang, Zhengliang; Guo, Junming; Wu, Mingmei
Abstract : The red Cs2 NaAl3 F12 :Mn 4+ phosphor with intense ZPL emission was obtained via the occupation of Mn 4+ for Al 3+, indicating its high colour purity and potential use in WLEDs. Abstract : In this work, a novel fluoroaluminate red phosphor of Cs2 NaAl3 F12 :Mn 4+ with excellent color purity was fabricated via the introduction of Mn 4+ in the octahedral center. The crystal and electronic structures, luminescence properties and optical performances were characterized and investigated in detail. The evidences showed that Cs2 NaAl3 F12 :Mn 4+ well-crystallized into a single phase with particulate morphology, and the non-equivalent occupation in Cs2 NaAl3 F12 resulted in sharp red emissions with improved color purity upon blue light illumination. For solid-state lighting, the optical parameters consisted of the "blue-yellow-red" contributions significantly improved to a high color-rendering index of 88.7 and a low color temperature of 3856 K, indicating the potential use of Cs2 NaAl3 F12 :Mn 4+ for warm white light-emitting diode applications.